The use of e-tests in education as a tool for retrieval practice and motivation - Papp Gabriella; Пап Габріелла (University of Debrecen, 2024)
Abstract. In many studies we can read about what techniques are used in the educational process to deepen knowledge, and what can motivate students to learn. We aimed to give our students (who will be a teacher) a practical demonstration of learning techniques. We carried it within the framework of a course, at the end of which we also examined how much it motivates students if they write an e-test as a retrospective in order to deepen the material of the lesson. In the paper, we will present the results of the research as well as students’ opinions regarding the motivating effect of the tests.
https://ojs.lib.unideb.hu/tmcs/article/view/13495
Keywords: retrieval practice; motivation; e-test; előhivásos tanulás; motiváció; e-teszt